ANALISIS SEPUTAR ZAKAT HASIL PERTANIAN (ZAKAT ZURU’) - Nurdin Manyak (Jurnal Tahqiqa : Jurnal Ilmiah Pemikiran Hukum Islam, 2013)
Today the application of science and technology in agriculture has beenable to make a variety of crops as a commodity that has economic value. In theold days such as vegetables, grown only in limited quantities for its own needsand not be traded, but are now growing vegetables has been professionallymanaged and has resulted in large numbers and even been used as commodityexports that generate a lot of money. Similarly, other agricultural products whichat first had no economic value, but today is can be used as a profitable item for theowner.